(untitled) (Research, Society and Development, 2022)
Objective: to verify the association between impairment of frailty phenotype components as predictors of mortality among older adults after four years of hospital discharge. Methodology: Prospective and longitudinal investigation, carried out with hospitalized older adults, at baseline, and followed up after hospital discharge. Of the 163 older adults included in the study, 43 died during follow-up and 92 completed the four-year follow-up. The following instruments were used: Mini Mental State Examination, a form for characterizing sociodemographic, economic and health data; and Fried’s frailty phenotype. Survival analysis was performed using the Kaplan-Meier method and Cox regression to estimate the risk ratio (Hazard Ratio) of mortality among older adults with impairment in each component of the phenotype, considering p<0.05. Results: The impairment in the components of the frailty phenotype slow gait speed (HR: 3.27; 95%CI: 1.655-6.475; p<0.001); decreased muscle strength (HR:3.09; 95%CI: 1.605-5.959; p=0.001); self-reported exhaustion and/or fatigue (HR: 2.97; 95%CI: 1.508-5.853; p=0.002) and low level of physical activity (HR: 3.22; 95%CI: 1.693-6.138; p<0.001) remained as predictors of mortality, after adjustment; and represented a lower probability of survival. Conclusion: Impairment in the components of gait speed, muscle strength, exhaustion and/or fatigue and physical activity at baseline represented a higher risk for mortality among the elderly at follow-up. Thus, there is the possibility of targeting interventions in risk groups to improve the condition of frailty and, consequently, increase survival.